Pengembangan Animasi Edukatif Berbasis Cerita Rakyat untuk Pelestarian Budaya Lokal - Atiqah Noor Zhaafirah; Adhisa Nanda Kurnia; Purwadi Purwadi (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the development of educational animation based on Indonesian folklore as a medium for preserving local culture. The method used is a systematic literature review (SLR) of various national and international journal publications from 2021 to 2025 that discuss educational animation, local wisdom, and cultural preservation. Data were collected from ScienceDirect, ResearchGate, and SINTA databases using the keywords “educational animation,” “folklore,” and “cultural preservation.” The data were analyzed qualitatively using content analysis and thematic mapping techniques to identify key themes and recent research directions. The results show that educational animation based on folklore significantly contributes to enhancing cultural awareness, character education, and student engagement in learning. Most studies emphasize that digital media—especially animation—play an important role in transmitting cultural and moral values to younger generations. However, research gaps remain, as most existing studies still focus on the entertainment aspect rather than educational integration. In conclusion, the development of educational animation based on folklore has the potential to serve as a strategic medium for intangible cultural heritage preservation while promoting creative and contextual learning in the digital era.